2011
DOI: 10.1021/bi201094v
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of the Human αC Region with the Analogous Chicken Domain Generates a Fibrinogen with Severely Impaired Lateral Aggregation: Fibrin Monomers Assemble into Protofibrils but Protofibrils Do Not Assemble into Fibers

Abstract: Fibrin polymerization occurs in two steps: the assembly of fibrin monomers into protofibrils and the lateral aggregation of protofibrils into fibers. Here we describe a novel fibrinogen that apparently impairs only lateral aggregation. This variant is a hybrid, where the human αC region has been replaced with the homologous chicken region. Several experiments indicate this hybrid human-chicken (HC) fibrinogen has an overall structure similar to normal. Thrombin-catalyzed fibrinopeptide release from HC fibrinog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…Dissociation and interaction of fibrinogen αC domains from the E region enables fibrin protofibril lateral aggregation during clot formation [36-38]. Alpha C double hairpin structures interact with adjacent and complementary hairpin structures on adjacent fibrin monomers to form large beta sheet structures, eventually coalescing into fibers [39].…”
Section: Discussionmentioning
confidence: 99%
“…Dissociation and interaction of fibrinogen αC domains from the E region enables fibrin protofibril lateral aggregation during clot formation [36-38]. Alpha C double hairpin structures interact with adjacent and complementary hairpin structures on adjacent fibrin monomers to form large beta sheet structures, eventually coalescing into fibers [39].…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that in fibrinogen two ␣C domains form a dimer through interaction with each other and the central region of the molecule. In polymeric fibrin, factor XIIIa covalently cross-links ␣C regions from different fibrin molecules to produce the fibrin network (41)(42)(43). It is speculated that the Gln acceptors located near the amino terminus of fibrin ␣C regions (␣C-connector) form cross-links with Lys donors located near the carboxyl terminus of ␣C regions (␣C domain) from another fibrin molecule (44).…”
Section: Discussionmentioning
confidence: 99%
“…Fibrinogen lacking the αC regions forms clots with thinner fibers and a higher density of branch points than clots made of full-length fibrinogen (Collet et al 2005). Furthermore, a recombinant fibrinogen construct that has the longer human αC regions replaced with the shorter chicken αC regions displayed impaired lateral aggregation of protofibrils (Ping et al 2011). …”
Section: 3 Molecular Mechanisms Of the Conversion Of Fibrinogen Tomentioning
confidence: 99%
“…The role of the αC polymers in fibrin mechanics, underestimated in the past, has been studied intensively more recently (Houser et al 2010; Falvo et al 2010; Ping et al 2011; Helms et al 2012; Averett et al 2012). It has been shown that the transglutaminase-catalyzed covalent crosslinking of the α chains contributes substantially to the fibrin clot stiffness and elasticity (Collet et al 1999; Piechocka et al 2010; Helms et al 2012; Duval et al 2014; Kurniawan et al 2014), including the fast elastic recoil of stretched fibrin fibers (Hudson et al 2013).…”
Section: 5 Fibrin Mechanical Properties and Their Structural Originsmentioning
confidence: 99%